Coconut shell-based foam carbon modified phosphate positive electrode material and application thereof

By using coconut-based foam charcoal to coat the phosphate positive electrode material, a three-dimensional conductive network is formed, which solves the problems of high and uneven carbon coating costs in the prior art, and significantly improves the rate performance and cycle life of lithium-ion batteries.

CN119812315AActive Publication Date: 2025-04-11SVOLT ENERGY TECHNOLOGY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510140026.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-08
Publication Date
2025-04-11
Estimated Expiration
2045-02-08

AI Technical Summary

Technical Problem

In the prior art, during the carbon coating process of phosphate positive electrode materials such as lithium manganese iron phosphate, the commonly used carbon materials such as graphene and carbon nanotubes are costly to produce, and it is easy to lead to uneven coating, which limits the performance improvement and application of phosphate positive electrode materials.

Method used

Coconut-based foam charcoal is used as the carbon source, and it is tightly and uniformly coated on the surface of the phosphate positive electrode material by coaxial electrospinning to form a three-dimensional conductive network to improve electronic conductivity and Li+ diffusion kinetics.

Benefits of technology

The electronic conductivity and Li+ diffusion kinetics of the phosphate positive electrode material have been significantly improved, the rate performance and cycle life of the lithium-ion battery are improved, and the electrode polarization effect and resistivity are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812315A_ABST
    Figure CN119812315A_ABST
Patent Text Reader

Abstract

The invention discloses a coconut shell-based foam carbon modified phosphate positive electrode material and application thereof. The positive electrode material comprises a phosphate positive electrode core and coconut shell-based foam carbon coated on the surface of the phosphate positive electrode core. The phosphate positive electrode core is coated with the coconut shell-based foam carbon with the light spongy structure, so that a three-dimensional conductive network can be formed among positive electrode material particles, the electronic conductivity among the phosphate positive electrode material particles is improved, the transmission of Li < + > / electrons is accelerated, the electrode polarization effect is reduced, and the resistivity of a pole piece is reduced. In addition, the foam carbon is coated on the surfaces of the positive electrode particles, so that particle aggregation can be inhibited, Li < + > diffusion kinetics is improved, and the rate capability of the lithium ion battery is greatly improved. Moreover, the coconut shell-based foam carbon on the surface of the main material can effectively inhibit the chemical reaction between the phosphate positive electrode material and an electrolyte to form a stable interface, so that the cycle life of the battery can be prolonged, and the battery shows excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries and relates to a coconut shell-based foamed carbon modified phosphate positive electrode material and application thereof. Background Art

[0002] In order to meet people's great demand for environmentally friendly, efficient and sustainable energy, the research and development of lithium-ion batteries with higher performance has attracted more and more attention. 4 Since the discovery of LiFePO (M = at least one of Fe, Mn, Co and Ni), there have been many achievements in this field in recent years. 4 Inspired by the successful commercialization of LiMnPO 4 It has been widely studied due to its higher electrode potential. Compared with LFP, LiMnPO 4 It has become one of the most promising positive electrode materials in the field of power batteries due to its high theoretical capacity, high voltage platform, low cost and environmental friendliness.

[0003] LiMnPO 4 As one of the most promising cathode active materials, LiMnPO has attracted much attention due to its high energy density, good safety performance and low cost. 4 Very low electronic conductivity (2-3 orders of magnitude lower than that of LFP) and Li + The slow diffusion of LiMnPO 4 The battery rate performance is poor. Moreover, during the electrochemical reaction, some manganese ions will undergo disproportionation reaction and dissolve in the electrolyte, resulting in poor battery cycle performance.

[0004] In order to improve the LiMnPO 4 The electrochemical performance of LiMnPO 4 Particles are refined to nanoscale to increase Li + The kinetics of diffusion can be controlled, thereby improving its rate performance. In addition, surface modification can also be used to prevent LiMnPO 4 Direct contact with the electrolyte inhibits side reactions and thus increases its cycle life.

[0005] CN118136813A discloses a coated lithium iron manganese phosphate material, its preparation method and application. The coated lithium iron manganese phosphate material includes lithium iron manganese phosphate nanoparticles, and the surfaces of the lithium iron manganese phosphate nanoparticles are coated with fluorine-doped amorphous carbon and graphene. By coating fluorine-doped amorphous carbon and graphene on the surfaces of the lithium iron manganese phosphate nanoparticles, a close-contact conductive network with "point-plane" combination is constructed. At the same time, the nanosized particles shorten the lithium ion migration path, thereby greatly improving the ion transport rate of the material, making its structure stable without collapse during repeated charge and discharge, and effectively alleviating the problem of manganese dissolution. Furthermore, it has excellent structural stability and electrical conductivity. When applied to lithium ion batteries, it can effectively improve the cycle performance and rate performance of lithium ion batteries.

[0006] CN116706020A discloses a lithium iron manganese phosphate cathode material and its preparation method. The lithium iron manganese phosphate cathode material includes an ionic conductor LiAlO 2 bulk coating layer and a LaF 3 / carbon surface coating layer. The mass fraction of the ionic conductor LiAlO 2 bulk coating layer is 0.5%-2%, the mass fraction of the carbon surface coating layer is 0.5%-2%, and the mass fraction of the LaF 3 surface coating layer is 1%-3%. By forming a carbon coating layer and a LaF 3 coating layer on the surface of the material, the electronic conductivity of the material can be improved, the side reaction between the electrolyte and the material can be inhibited, the dissolution of transition metals in the material can be inhibited, and the impedance growth during the battery cycle can be inhibited.

[0007] CN118738326A discloses a lithium iron manganese phosphate co-coated with nanoscale lithium phosphate and a carbon layer, its preparation and application. The preparation method includes the following steps: Step 1, weigh a lithium iron manganese phosphate LiMn x Fe 1-x PO 4 precursor, 1%-8% of nanoscale lithium phosphate, 10%-20% of a carbon source, and 1%-5% of an antioxidant by mass percentage of the lithium iron manganese phosphate, and mix them evenly. 0 < x < 1; Step 2, sinter the evenly mixed material obtained in Step 1 at 600°C - 800°C in an inert atmosphere, keep it warm for 4h - 12h, and then naturally cool to room temperature to obtain the lithium iron manganese phosphate co-coated with lithium phosphate and a carbon layer. This method combines a simple ball milling process with solid-phase sintering synthesis. By utilizing the complementary structural properties of nanoscale lithium phosphate and the carbon layer, the coating layer is made more complete to better protect the lithium iron manganese phosphate material, thereby avoiding contact with the electrolyte during its application and reducing side reactions. At the same time, a good coating effect can reduce Mn 3+The lattice distortion caused by the induced Jahn-Teller effect relieves the stress generated by the positive electrode material during phase change during the charge and discharge process, improves the structural stability of the positive electrode material, and thus improves the cycle stability and service life of the battery; and, since lithium phosphate has good stability and ionic conductivity, it improves the ionic and electronic conductivity of the positive electrode material and increases the lithium ion migration rate.

[0008] However, when carbon-coating phosphate cathode materials such as lithium manganese iron phosphate, carbon materials such as graphene and carbon nanotubes are often used. Their preparation cost is high and they are prone to uneven coating problems, which limits the performance improvement and application of phosphate cathode materials. Summary of the invention

[0009] In view of the above technical problems existing in the prior art, the object of the present invention is to provide a coconut shell-based foamed carbon modified phosphate positive electrode material and application thereof.

[0010] To achieve the above object, the present invention adopts the following technical solutions:

[0011] In a first aspect, the present invention provides a coconut shell-based foamed carbon modified phosphate positive electrode material, wherein the positive electrode material comprises a phosphate positive electrode core and a coconut shell-based foamed carbon coated on the surface of the phosphate positive electrode core.

[0012] In the present invention, coconut shell-based foamed carbon refers to a foamed carbon material prepared from coconut shell as a raw material, which has the advantages of low density, high strength, electrical conductivity, thermal conductivity, thermal stability, chemical stability, etc. The present invention uses a lightweight sponge-like structure of coconut shell-based foamed carbon to coat the phosphate positive electrode core, which can form a three-dimensional conductive network between the positive electrode material particles, thereby improving the conductivity of the phosphate positive electrode material (such as LiMnPO 4 ) The electronic conductivity between particles accelerates the Li + / electron transfer, reducing electrode polarization effect and lowering the resistivity of the electrode. In addition, carbon foam coated on the surface of positive electrode particles can inhibit particle agglomeration and improve Li + Diffusion dynamics greatly improves the rate performance of lithium-ion batteries. Moreover, the coconut shell-based foamed carbon on the surface of the main material can effectively inhibit the chemical reaction between the phosphate positive electrode material and the electrolyte, forming a stable interface, thereby increasing the cycle life of the battery and making the battery exhibit excellent electrochemical performance.

[0013] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0014] Preferably, based on the total mass of the positive electrode material as 100%, the mass fraction of the coconut shell-based foamed carbon is 2%-3%, for example, it can be 2%, 2.1%, 2.2%, 2.3%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9% or 3%, etc.

[0015] In a second aspect, the present invention provides a method for preparing the coconut shell-based foamed carbon modified phosphate positive electrode material as described in the first aspect, the preparation method comprising the following steps:

[0016] (1) preparing coconut shell-based foamed carbon;

[0017] (2) The phosphate positive electrode material is formed into a core slurry, and the coconut shell-based foamed carbon is formed into a shell slurry. The core slurry and the shell slurry are used for coaxial electrospinning to obtain the coconut shell-based foamed carbon modified phosphate positive electrode material.

[0018] The method of the present invention uses coconut shell as a raw material to prepare coconut shell-based foamed carbon with a sponge-like structure as a carbon source. Coconut shell is widely available and can greatly reduce production costs. Moreover, the morphology and performance of the coconut shell-based foamed carbon with a sponge-like structure are very beneficial to the coating of phosphate positive electrode materials. The core-shell structure is prepared by coaxial electrospinning, and the coconut shell-based foamed carbon is tightly and evenly coated on the surface of the phosphate positive electrode core. Compared with the method of directly mixing the carbon source with the phosphate positive electrode material and then sintering in the prior art, the method has the following advantages: the carbon coating layer is more uniform and complete, which is beneficial to improving the processability of the positive electrode slurry, as well as the rate performance and cycle life of the battery.

[0019] The method of the invention is environmentally friendly, has a simple preparation process, a short preparation cycle, low preparation cost, and is suitable for industrial production.

[0020] As a preferred technical solution of the preparation method of the present invention, the preparation method of coconut shell-based foamed carbon in step (1) comprises the following steps:

[0021] (a) pre-treating coconut shell to obtain coconut shell powder;

[0022] (b) mixing coconut shell powder with an aldehyde substance and concentrated acid to obtain a mixed slurry, placing the mixed slurry in a reaction kettle, charging with a protective gas and performing a heating reaction to obtain a foamed coconut shell resin;

[0023] (c) heat-treating the foamed coconut shell resin to obtain coconut shell-based foamed charcoal.

[0024] In the method of the present invention, aldehyde substances are used as carbon sources, and concentrated acid can play an activation role, promoting the cracking and activation of foamed carbon, thereby generating more micropores and mesopores, increasing the porosity of the material, and removing inorganic impurities in the foamed carbon, thereby improving the purity of the foamed carbon.

[0025] In the present invention, concentrated acid refers to an acid substance having a molar concentration greater than or equal to 10 mol / L, for example, 10 mol / L, 10.5 mol / L, 11 mol / L, 12 mol / L, 13 mol / L, 14 mol / L, 15 mol / L or 16 mol / L, etc. Preferably, the pretreatment in step (a) is crushing and screening.

[0026] Preferably, in step (b), the aldehyde substance comprises at least one of formaldehyde, octanal, nonanal, decanal and undecanal.

[0027] Preferably, in step (b), the mass ratio of the coconut shell powder to the aldehyde substance is (5-15):1, for example, it can be 5:1, 5.5:1, 6:1, 6.5:1, 7:1, 7.5:1, 8:1, 8.5:1, 9:1, 9.5:1, 10:1, 10.5:1, 11:1, 11.5:1, 12:1, 12.5:1, 13:1, 13.5:1, 14:1 or 15:1, etc.

[0028] Preferably, the concentrated acid in step (b) comprises at least one of concentrated sulfuric acid, concentrated sulfuric acid and concentrated nitric acid.

[0029] Preferably, the concentration of the mixed slurry in step (b) is 1.5 mol / L-2 mol / L, for example, it can be 1.5 mol / L, 1.6 mol / L, 1.7 mol / L, 1.8 mol / L, 1.9 mol / L or 2 mol / L.

[0030] Preferably, the heating reaction in step (b) includes two stages, wherein the first stage is: heating to a first temperature and keeping it warm; the second stage is: continuing to heat to a second temperature and keeping it warm.

[0031] The purpose of carrying out hydrothermal treatment in two stages is to make the foaming more uniform, the particle size of the prepared foamed carbon more uniform, and to obtain foamed carbon of higher purity.

[0032] Preferably, the first temperature is 300°C-400°C, for example, it can be 300°C, 320°C, 340°C, 350°C, 360°C, 380°C or 400°C; the insulation time at the first temperature is 12h-36h, for example, it can be 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h, 25h, 26h, 27h, 28h, 29h, 30h, 31h, 32h, 33h, 34h, 35h or 36h.

[0033] Preferably, the second temperature is 500°C-650°C, for example, it can be 500°C, 525°C, 550°C, 560°C, 570°C, 580°C, 600°C, 620°C, 630°C or 650°C, etc.; the insulation time at the second temperature is 5h-10h, for example, it can be 5h, 6h, 7h, 8h, 9h or 10h, etc.

[0034] Preferably, the pressure of the heating reaction in step (b) is 1 MPa-5 MPa, for example, it can be 1 MPa, 1.5 MPa, 2 MPa, 2.5 MPa, 3 MPa, 3.5 MPa, 4 MPa, 4.5 MPa or 5 MPa.

[0035] Preferably, the temperature of the heat treatment in step (c) is 700°C-800°C, for example, it can be 700°C, 720°C, 740°C, 760°C, 780°C or 800°C.

[0036] Preferably, the heat treatment time in step (c) is 3 h to 6 h, for example, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h or 6 h.

[0037] In the present invention, the preparation method of the phosphate positive electrode material is not specifically limited, and those skilled in the art can prepare it according to the method disclosed in the prior art, for example, it can be a sol-gel-casting method.

[0038] As a preferred technical solution of the preparation method of the present invention, the core slurry in step (2) is obtained by dispersing the phosphate positive electrode material and the first surfactant in an organic solvent. The addition of the surfactant is beneficial to improving the bonding effect of the phosphate positive electrode material and the coconut shell-based foamed carbon in the subsequent steps.

[0039] Preferably, the first surfactant includes at least one of polyurethane and hexadecyltrimethylammonium bromide (CTAB).

[0040] Preferably, the mass ratio of the phosphate positive electrode material to the first surfactant is 90:(0.5-1.5), for example, it can be 90:0.5, 90:0.6, 90:0.7, 90:0.8, 90:1, 90:1.2, 90:1.3, 90:1.4 or 90:1.5, etc.; the concentration of the core slurry is 6mol / L-8mol / L, for example, it can be 6mol / L, 6.5mol / L, 7mol / L, 7.5mol / L or 8mol / L, etc.

[0041] Preferably, the shell slurry is obtained by dispersing coconut shell-based foamed carbon and a second surfactant in an organic solvent. Adding the surfactant is beneficial to improving the combination effect of the phosphate positive electrode material and the coconut shell-based foamed carbon in the subsequent steps.

[0042] Preferably, the second surfactant comprises at least one of polyurethane and CTAB.

[0043] In the present invention, the "first" and "second" in "first surfactant" and "second surfactant" have no substantial meaning and are only used as a distinction in names. The first surfactant and the second surfactant may be of the same or different types.

[0044] Preferably, the mass ratio of the coconut shell-based foamed carbon and the second surfactant is 80:(0.5-1.5), for example, it can be 80:0.5, 80:0.6, 80:0.7, 80:0.8, 80:0.9, 80:1, 80:1.1, 80:1.2, 80:1.3, 80:1.4 or 80:1.5, etc.; the concentration of the shell slurry is 1.5mol / L-2mol / L, for example, it can be 1.5mol / L, 1.6mol / L, 1.7mol / L, 1.8mol / L, 1.9mol / L or 2mol / L, etc.

[0045] The present invention can make the carbon coating of the phosphate positive electrode material more uniform and complete by regulating the composition of the core slurry and the shell slurry, which is beneficial to improving the processability of the positive electrode slurry, as well as the rate performance, cycle life and other properties of the battery.

[0046] Preferably, the voltage of the coaxial electrospinning in step (2) is 20 kV-40 kV, for example, it can be 20 kV, 22 kV, 23 kV, 25 kV, 26 kV, 28 kV, 30 kV, 32 kV, 34 kV, 36 kV, 38 kV or 40 kV.

[0047] Preferably, the spinning rate of the coaxial electrospinning in step (2) is 5 mL / min-15 mL / min, for example, it can be 5 mL / min, 6 mL / min, 8 mL / min, 9 mL / min, 10 mL / min, 12 mL / min, 13 mL / min or 15 mL / min, etc.

[0048] Preferably, the method further comprises the steps of washing and spray drying the product after the electrospinning in step (2).

[0049] In a third aspect, the present invention provides a positive electrode slurry, which is obtained by homogenizing the coconut shell-based foamed carbon modified phosphate positive electrode material described in the first aspect. Since the positive electrode slurry is prepared using the positive electrode material of the first aspect, the processing performance of the positive electrode slurry is good.

[0050] In a fourth aspect, the present invention provides a method for homogenizing the positive electrode slurry as described in the third aspect, the homogenization method comprising the following steps:

[0051] After mixing the coconut shell-based foam carbon modified phosphate positive electrode material with the conductive agent and the binder, adding an organic solvent at least three times, stirring after each addition of the organic solvent, to obtain a positive electrode slurry;

[0052] The amount of organic solvent added in the latter step is greater than the amount of organic solvent added in the previous step.

[0053] The present invention effectively increases the solid content of the slurry by optimizing the homogenization process, greatly reduces the use of organic solvents (such as NMP), and thus achieves the purpose of reducing costs. At the same time, the process improves the processability of the slurry, enhances the dispersibility of the slurry, effectively reduces the resistivity of the pole piece, reduces the aging internal resistance of the battery, and is beneficial to the performance of the battery.

[0054] In a fifth aspect, the present invention provides a positive electrode, which is prepared using the positive electrode slurry described in the third aspect.

[0055] In a sixth aspect, the present invention provides a battery, comprising the positive electrode described in the fifth aspect.

[0056] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0057] Compared with the prior art, the present invention has the following beneficial effects:

[0058] (1) The present invention uses a lightweight sponge-like structure of coconut shell-based foamed carbon to coat the phosphate positive electrode core, which can form a three-dimensional conductive network between the positive electrode material particles, thereby improving the conductivity of the phosphate positive electrode material (such as LiMnPO 4 ) The electronic conductivity between particles is improved, the transfer of Li+ / electrons is accelerated, the electrode polarization effect is reduced, and the resistivity of the electrode sheet is reduced. In addition, the carbon foam coated on the surface of the positive electrode particles can inhibit particle agglomeration, improve the Li+ diffusion kinetics, and greatly improve the rate performance of lithium-ion batteries. Moreover, the coconut shell-based carbon foam on the surface of the main material can effectively inhibit the chemical reaction between the phosphate positive electrode material and the electrolyte, forming a stable interface, thereby improving the cycle life of the battery and making the battery exhibit excellent electrochemical performance.

[0059] (2) The method of the present invention uses coconut shell as a raw material to prepare a carbon source. Coconut shell has a wide source, which can greatly reduce the production cost. Moreover, the morphology and properties of the coconut shell-based foam carbon with a sponge-like structure are very beneficial to the coating of the phosphate cathode material. By using the coaxial electrospinning method to prepare a core-shell structure, the coconut shell-based foam carbon is tightly and uniformly coated on the surface of the phosphate cathode core. Compared with the method of directly mixing the carbon source with the phosphate cathode material and then sintering in the prior art, it has the following advantages: the carbon coating layer is more uniform and complete, which is beneficial to improving the processability of the cathode slurry, as well as the rate performance and cycle life of the battery, etc.

[0060] (3) The method of the present invention is environmentally friendly, has a simple preparation process, a short preparation period, and a low preparation cost, and is suitable for industrial production. Description of the Drawings

[0061] Figure 1 The structural schematic diagram of the coconut shell-based foam carbon modified LiMnPO 4 material provided by an embodiment of the present invention, wherein 1 is LiMnPO 4 core, and 2 is coconut shell-based foam carbon. Detailed Embodiments

[0062] The technical solution of the present invention will be further described below with reference to the drawings and through specific embodiments.

[0063] The specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0064] Example 1

[0065] This example provides a coconut shell-based foam carbon modified LiMnPO 4 material (abbreviated as LiMnPO 4 @coconut shell-based foam carbon composite material), and its structural schematic diagram is shown in Figure 1 , including LiMnPO 4 core 1 and coconut shell-based foam carbon 2 coated on the surface of LiMnPO 4 core 1. Based on the total mass of the coconut shell-based foam carbon modified LiMnPO 4 material being 100%, the mass fraction of the coconut shell-based foam carbon 2 is 2.5%.

[0066] This example also provides a preparation method for the above-mentioned coconut shell-based foam carbon modified LiMnPO 4 material, including the following steps:

[0067] (1) Prepare LiMnPO 4 by the sol-gel casting method. The specific preparation method is as follows:

[0068] ① 1 mol of Li 2 CO 3 , 2 mol of MnCl 2 , 2 mol (NH 4 ) 3 PO 4 and an appropriate amount of dichloromethane, and stirred to mix evenly, wherein the mass of dichloromethane is Li 2 CO 3 、MnCl 2 and (NH 4 ) 3 PO 4 2 times the sum of the mass, then add 1 mmol of benzalkonium chloride, place the mixture in a water bath at 80°C and stir for 4 hours at a stirring speed of 600 rpm / min, cool to room temperature after stirring, and then evenly apply it on a glass slide with a rubber dropper;

[0069] ② Move the coated slide into a vacuum drying oven and keep it at 100℃ for 10h;

[0070] ③ Peel the product obtained in ② off the glass slide and grind it;

[0071] ④ The ground powder was sieved with a 250-mesh sieve, and the sieved powder was placed in a tube furnace, heated to 800°C at a heating rate of 10°C / min under a nitrogen atmosphere and kept warm for 6 hours. After the insulation, it was cooled to room temperature to obtain LiMnPO 4 .

[0072] (2) Preparation of coconut shell-based foamed carbon, the specific preparation method is:

[0073] ① The coconut shell was crushed and sieved (250 mesh screen), and then the sieved powder and formaldehyde were placed in concentrated phosphoric acid (concentration of 14.7 mol / L) at a mass ratio of 10:1 to obtain a mixed slurry. The concentration of the mixed slurry was 1.5 mol / L. The mixture was stirred evenly and then placed in a high-pressure reactor, filled with nitrogen protective atmosphere, heated to 350°C and kept warm for 24 hours. The gas pressure in the high-pressure reactor was 2 MPa;

[0074] ②Put the product obtained in ① into a high-temperature and high-pressure reactor, fill it with nitrogen protective atmosphere, heat it to 600℃ and keep it for 8h. The gas pressure in the high-pressure reactor is 2MPa. After the reaction is completed, cool it to room temperature to obtain foamed coconut shell resin;

[0075] ③ The product obtained in step ② is placed in a tubular furnace, nitrogen is introduced for protection, heated to 700°C and kept warm for 4 hours, the gas pressure in the high-pressure reactor is 2MPa, and then naturally cooled to room temperature to obtain coconut shell-based foamed carbon.

[0076] (3) Preparation of LiMnPO by coaxial electrospinning 4 @Coconut shell-based foam carbon composite material, the specific preparation method is:

[0077] ① Ultrasonically uniformly dispersing the coconut shell-based foamed carbon and polyurethane (the mass ratio of coconut shell-based foamed carbon to polyurethane is 80:1) obtained in step (2) in an ethylene glycol monomethyl ether solution to obtain a shell slurry with a concentration of 2 mol / L;

[0078] ② LiMnPO obtained in step (1) 4 Nanoparticles and polyurethane (LiMnPO 4 The nanoparticles and polyurethane were ultrasonically dispersed in an ethylene glycol monomethyl ether solution at a mass ratio of 90:1 to obtain a core slurry with a concentration of 7 mol / L;

[0079] ③ The electrospinning solutions (i.e., shell slurry and core slurry) obtained in steps ① and ② are placed in two feeding ports of the electrospinning machine respectively, and the shell slurry and core slurry flow out from different channels of the coaxial nozzle respectively. Under the action of a high voltage electric field (voltage of 30 kV), the spinning rate is 10 mL / min, and the two solutions spontaneously form particles at the same time, thereby forming a composite material with a core-shell structure;

[0080] ④ The product obtained in step ③ was washed with deionized water and anhydrous ethanol for 6 times, and then spray-dried to obtain LiMnPO 4 @Coconut shell-based foam carbon composite material, that is, coconut shell-based foam carbon modified LiMnPO 4 Material.

[0081] Example 2

[0082] This embodiment provides a coconut shell-based foam carbon modified LiMnPO 4 Material (LiMnPO 4 @Coconut shell-based foam carbon composites), including LiMnPO 4 The core and the coating are LiMnPO 4 Coconut shell-based foam carbon on the surface of the core, and LiMnPO modified by the coconut shell-based foam carbon 4 The total mass of the material is 100%, and the mass fraction of the coconut shell-based foamed carbon is 2.5%.

[0083] This embodiment also provides the above-mentioned coconut shell-based foam carbon modified LiMnPO 4 The method for preparing the material comprises the following steps:

[0084] (1) Preparation of LiMnPO by sol-gel-casting method 4 , the preparation method is the same as Example 1.

[0085] (2) Preparation of coconut shell-based foamed carbon, the specific preparation method is:

[0086] ① The coconut shell was crushed and sieved (250 mesh screen), and then the sieved powder and formaldehyde were placed in concentrated phosphoric acid (concentration of 14.7 mol / L) at a mass ratio of 5:1 to obtain a mixed slurry. The concentration of the mixed slurry was 2 mol / L. The mixture was stirred evenly and then placed in a high-pressure reactor filled with nitrogen protective atmosphere, heated to 300 ° C for 36 hours, and the gas pressure in the high-pressure reactor was 2 MPa;

[0087] ②Put the product obtained in ① into a high-temperature and high-pressure reactor, fill it with nitrogen protective atmosphere, heat it to 650℃ and keep it for 5h. The gas pressure in the high-pressure reactor is 2MPa. After the reaction is completed, cool it to room temperature to obtain foamed coconut shell resin;

[0088] ③ The product obtained in step ② is placed in a tubular furnace, nitrogen is introduced for protection, heated to 750°C and kept warm for 4 hours, the gas pressure in the high-pressure reactor is 2MPa, and then naturally cooled to room temperature to obtain coconut shell-based foamed carbon.

[0089] (3) Preparation of LiMnPO by coaxial electrospinning 4 @Coconut shell-based foam carbon composite material, the specific preparation method is:

[0090] ① Ultrasonically uniformly dispersing the coconut shell-based foamed carbon and polyurethane (the mass ratio of coconut shell-based foamed carbon to polyurethane is 80:1.5) obtained in step (2) in an ethylene glycol monomethyl ether solution to obtain a shell slurry with a concentration of 1.5 mol / L;

[0091] ② LiMnPO obtained in step (1) 4 Nanoparticles and polyurethane (LiMnPO 4 The nanoparticles and polyurethane were ultrasonically dispersed in an ethylene glycol monomethyl ether solution in a mass ratio of 90:1.5 to obtain a core slurry with a concentration of 6 mol / L;

[0092] ③ The electrospinning solutions (i.e., shell slurry and core slurry) obtained in steps ① and ② are placed in two feeding ports of the electrospinning machine respectively, and the shell slurry and core slurry flow out from different channels of the coaxial nozzle respectively. Under the action of a high voltage electric field (voltage of 20 kV), the spinning rate is 5 mL / min, and the two solutions spontaneously form particles at the same time, thereby forming a composite material with a core-shell structure;

[0093] ④ The product obtained in step ③ was washed with deionized water and anhydrous ethanol for 6 times, and then spray-dried to obtain LiMnPO 4 @Coconut shell-based foam carbon composite material, that is, coconut shell-based foam carbon modified LiMnPO 4 Material.

[0094] Example 3

[0095] This embodiment provides a coconut shell-based foam carbon modified LiMnPO 4 Material (LiMnPO 4 @Coconut shell-based foam carbon composites), including LiMnPO 4 The core and the coating are LiMnPO 4 Coconut shell-based foam carbon on the surface of the core, and LiMnPO modified by the coconut shell-based foam carbon 4 The total mass of the material is 100%, and the mass fraction of the coconut shell-based foamed carbon is 2.5%.

[0096] This embodiment also provides the above-mentioned coconut shell-based foam carbon modified LiMnPO 4 The method for preparing the material comprises the following steps:

[0097] (1) Preparation of LiMnPO by sol-gel-casting method 4 , the preparation method is the same as Example 1.

[0098] (2) Preparation of coconut shell-based foamed carbon, the specific preparation method is:

[0099] ① The coconut shell was crushed and sieved (250 mesh screen), and then the sieved powder and formaldehyde were placed in concentrated phosphoric acid (concentration of 14.7 mol / L) at a mass ratio of 15:1 to obtain a mixed slurry. The concentration of the mixed slurry was 1.7 mol / L. The mixture was stirred evenly and then placed in a high-pressure reactor filled with nitrogen protective atmosphere, heated to 400°C for 12 hours, and the gas pressure in the high-pressure reactor was 2 MPa;

[0100] ②Put the product obtained in ① into a high-temperature and high-pressure reactor, fill it with nitrogen protective atmosphere, heat it to 500℃ and keep it for 10h. The gas pressure in the high-pressure reactor is 2MPa. After the reaction is completed, cool it to room temperature to obtain foamed coconut shell resin;

[0101] ③ The product obtained in step ② is placed in a tubular furnace, nitrogen is introduced for protection, heated to 800° C. and kept warm for 3 h, and then naturally cooled to room temperature to obtain coconut shell-based foamed carbon.

[0102] (3) Preparation of LiMnPO by coaxial electrospinning 4 @Coconut shell-based foam carbon composite material, the specific preparation method is:

[0103] ① Ultrasonically uniformly dispersing the coconut shell-based foamed carbon and polyurethane (the mass ratio of coconut shell-based foamed carbon to polyurethane is 80:0.5) obtained in step (2) in an ethylene glycol monomethyl ether solution to obtain a shell slurry with a concentration of 1.8 mol / L;

[0104] ② LiMnPO obtained in step (1) 4 Nanoparticles and polyurethane (LiMnPO 4 The nanoparticles and polyurethane were ultrasonically dispersed in an ethylene glycol monomethyl ether solution in a mass ratio of 90:0.5 to obtain a core slurry with a concentration of 6.5 mol / L;

[0105] ③ The electrospinning solutions (i.e., shell slurry and core slurry) obtained in steps ① and ② are placed in two feeding ports of the electrospinning machine respectively, and the shell slurry and core slurry flow out from different channels of the coaxial nozzle respectively. Under the action of a high voltage electric field (voltage of 40 kV), the spinning rate is 15 mL / min, and the two solutions spontaneously form particles at the same time, thereby forming a composite material with a core-shell structure;

[0106] ④ The product obtained in step ③ was washed with deionized water and anhydrous ethanol for 5 times, and then spray-dried to obtain LiMnPO 4 @Coconut shell-based foam carbon composite material, that is, coconut shell-based foam carbon modified LiMnPO 4 Material.

[0107] Example 4

[0108] This embodiment provides a coconut shell-based foam carbon modified LiMnPO 4 The material and preparation method thereof are different from those of Example 1 in that the concentration of the shell slurry in step (3) is changed to make the coconut shell-based foamed carbon modified LiMnPO 4 The mass fraction of coconut shell-based foamed carbon in the material is 1.2%.

[0109] Example 5

[0110] This embodiment provides a coconut shell-based foam carbon modified LiMnPO 4 The material and preparation method thereof are different from those of Example 1 in that the concentration of the shell slurry in step (3) is changed to make the coconut shell-based foamed carbon modified LiMnPO 4 The mass fraction of coconut shell-based foamed carbon in the material is 3.6%.

[0111] Example 6

[0112] This embodiment provides a coconut shell-based foam carbon modified LiMnPO 4 Materials and preparation methods thereof, wherein the preparation method thereof is different from that of Example 1 in that, in step (2), steps ①-② are adjusted to:

[0113] The coconut shell was crushed and sieved (250 mesh sieve), and then the sieved powder and formaldehyde were placed in concentrated phosphoric acid (concentration of 14.7 mol / L) at a mass ratio of 10:1 to obtain a mixed slurry. The concentration of the mixed slurry was 1.5 mol / L. The slurry was stirred evenly, and then placed in a high-pressure reactor filled with nitrogen protective atmosphere, heated to 350°C and kept warm for 24 hours. The gas pressure in the high-pressure reactor was 2 MPa. After the reaction was completed, it was cooled to room temperature to obtain foamed coconut shell resin.

[0114] Example 7

[0115] This embodiment provides a coconut shell-based foam carbon modified LiMnPO 4 Materials and preparation methods thereof, wherein the preparation method thereof is different from that of Example 1 in that, in step (2), steps ①-② are adjusted to:

[0116] ① The coconut shell is crushed and sieved (250 mesh sieve), and then the sieved powder and formaldehyde are placed in concentrated phosphoric acid (concentration 14.7 mol / L) at a mass ratio of 10:1 to obtain a mixed slurry. The concentration of the mixed slurry is 1.5 mol / L. It is stirred evenly and then placed in a high-temperature and high-pressure reactor, filled with nitrogen protective atmosphere, heated to 600°C and kept warm for 8 hours. The gas pressure in the high-pressure reactor is 2 MPa. After the reaction is completed, it is cooled to room temperature to obtain foamed coconut shell resin.

[0117] Comparative Example 1

[0118] This comparative example provides unmodified LiMnPO 4 Material.

[0119] Comparative Example 2

[0120] This comparative example provides a carbon-coated LiMnPO 4 Materials (LiMnPO 4 / C material), which uses glucose as a carbon source for carbon coating, and the specific preparation method is:

[0121] 1 g of glucose was mixed with 100 g of DMF and heated at 60 °C for 8 h to form a transparent solution. 4 Add it to the transparent solution of glucose and DMF, stir it magnetically at room temperature for 12 hours to form a uniform dispersion; then heat it at 150°C and stir it, evaporate the solvent to obtain a powder of the two uniformly mixed; place the obtained powder in an argon atmosphere tube furnace, heat it to 600°C at a rate of 2°C / min and calcine it for 6 hours, and then cool it to obtain the product LiMnPO 4 / C material.

[0122] Comparative Example 3

[0123] This comparative example provides a carbon-coated LiMnPO 4 The material, the preparation method thereof is different from that of Example 1 in that the coconut shell-based foamed carbon is replaced with a peanut shell-based carbon material, and the preparation method of the peanut shell-based carbon material is as follows:

[0124] The peanut shells were crushed and passed through a 250-mesh sieve. The sieved powder was then placed in a 14 mol / L concentrated sulfuric acid solution and kept at 80°C for 1 hour. The powder was then washed and dried. The powder was carbonized at 350°C for 24 hours under nitrogen protection to obtain a peanut shell-based carbon material.

[0125] In some other embodiments, the present invention provides a positive electrode slurry and a homogenization process thereof, wherein the homogenization process comprises: modifying LiMnPO 4 The material is mixed with a conductive agent and a binder, and then an organic solvent is added thereto three times, and stirring is performed after each addition of the organic solvent to obtain a positive electrode slurry; wherein the amount of organic solvent added in the latter addition is greater than the amount of organic solvent added in the previous addition.

[0126] Embodiment 8-14

[0127] Provided is a positive electrode slurry, wherein the homogenization process is as follows: the coconut shell-based foam carbon modified LiMnPO prepared in Examples 1-7 is respectively 4 The material is mixed with a conductive agent (Super P) and a binder (PVDF) in a mass ratio of 8:1:1, and then an organic solvent NMP is added thereto three times, and stirring is performed after each addition of the organic solvent to obtain a positive electrode slurry; wherein the NMP added sequentially is 1 / 4, 1 / 3 and 5 / 12 of the total NMP mass.

[0128] Comparative Example 1

[0129] A positive electrode slurry is provided, and its homogenization process is a conventional homogenization process, specifically: the coconut shell-based foam carbon modified LiMnPO prepared in Example 1 is used 4 The material is mixed with a conductive agent (Super P), a binder (PVDF) and NMP, wherein the coconut shell-based foam carbon modified LiMnPO 4 The mass ratio of the material to Super P and PVDF is 8:1:1, and then NMP is added to adjust the slurry viscosity to obtain the positive electrode slurry.

[0130] Comparative Example 2

[0131] A positive electrode slurry is provided, which is different from Example 8 in that the coconut shell-based foam carbon modified LiMnPO 4 The material was replaced by the unmodified LiMnPO of Comparative Example 1. 4 Material.

[0132] The processing performance test was performed on the positive electrode slurries of Example 8, Comparative Example 1 and Comparative Example 2:

[0133] (1) The viscosity was tested using a rotational viscometer at 25°C, a 64# rotor, and a rotation speed of 60 rpm. Each slurry was tested three times to obtain the average value and record the viscosity of the slurry.

[0134] (2) Use a solid content meter to test the solid content. Perform three tests on each slurry and take the average value. Record the viscosity of the slurry.

[0135] The results are shown in Table 1.

[0136] Table 1

[0137]

[0138] Combined with Table 1, by comparing Example 8 with Control Example 1, it can be seen that compared with the conventional homogenization process, the homogenization process of the present invention can reduce the amount of NMP used and effectively improve the coconut shell-based foam carbon modified LiMnPO 4 The solid content of the positive electrode slurry made of the material is increased by 3%. By comparing Example 1 with Control Example 2, it can be seen that the positive electrode material in the positive electrode slurry is coconut shell-based foam carbon modified LiMnPO 4 materials, compared to unmodified LiMnPO 4 , the slurry viscosity was lower and the solid content was increased by 6.2%.

[0139] Application Example 1

[0140] A battery is provided, and a method for manufacturing the battery is as follows:

[0141] (I) Preparation of positive electrode sheet: The positive electrode slurry of Example 8 is evenly coated on an aluminum foil current collector, dried, and then rolled and die-cut into positive electrode sheets for small soft-pack batteries.

[0142] (II) Preparation of negative electrode sheet: Graphite, carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber are mixed evenly in a mass ratio of 8:1:0.6:0.4 and then coated on the surface of copper foil. After drying, the mixture is rolled and die-cut to form a negative electrode sheet.

[0143] (III) With glass fiber as separator, 1 mol / L LiPF 6 / EC-DEC-DMC (volume ratio of 1:1:1) is the electrolyte.

[0144] Finally, the negative electrode sheet-diaphragm-positive electrode sheet-diaphragm are stacked in order from top to bottom to obtain an electrode group. The bare battery cell is placed in an aluminum-plastic film outer packaging shell, and the electrolyte is injected after drying. After vacuum packaging, welding, standing and formation, the test battery is obtained.

[0145] Application Example 2-7

[0146] A battery is provided, and its manufacturing method is different from that of Application Example 1 in that the positive electrode slurry of Example 8 is replaced by the positive electrode slurries of Examples 9-14 respectively.

[0147] Application Comparative Examples 1-3

[0148] A battery is provided, and its manufacturing method is different from that of Application Example 1 in that the positive electrode slurry of Example 8 is replaced by the positive electrode slurries of Comparative Examples 1-3 respectively.

[0149] The following tests are performed on Use Case 1 and Comparative Example 1:

[0150] (1) Test step (I) The surface resistance of the positive electrode sheet prepared is tested by first measuring the thickness of the positive electrode sheet with a micrometer, then pressing the probe of the four-probe tester vertically and lightly on the surface of the positive electrode sheet, applying pressure evenly, inputting the instrument test parameters (current, four-probe spacing) and then starting the test, and finally obtaining the test results of the electrode sheet surface resistance. The test results are shown in Table 2.

[0151] (2) The internal resistance of the test battery after formation is recorded as the aged internal resistance, see Table 2.

[0152] Table 2

[0153]

[0154] Combined with Table 2, by comparison, it can be seen that the positive electrode material is selected from coconut shell-based foam carbon modified LiMnPO 4 materials, compared to unmodified LiMnPO 4 The surface resistance of the prepared positive electrode sheet decreased by 30.8%.

[0155] At the same time, the internal resistance of the battery made with this positive electrode sheet decreased by 24.5% after formation.

[0156] The following tests were performed on the batteries of the corresponding use cases 1-7 and the comparative examples 1-3:

[0157] (1) First-effect test: After full charging at 0.33C constant current and constant voltage, record the charging capacity. Then, discharge at 0.33C constant current to 2.5V and record the discharge capacity. The first effect is the ratio of the discharge capacity to the charging capacity.

[0158] (2) 3C constant current charging ratio test: The battery is charged to 3.65V at 0.33C constant current and constant voltage, then discharged at 0.33C, and the discharge capacity C0 is recorded. After that, it is fully charged at 3C constant current and constant voltage, and the charge capacity C1 is recorded. C1 / C0 is the constant current charging ratio.

[0159] (3) 3C / 0.33C ratio test: The battery is charged at 0.33C constant current and constant voltage to 3.65V, then discharged at 0.33C and the discharge capacity C0 is recorded. After that, it is fully charged at 0.33C constant current and constant voltage. After full charge, it is discharged at 0.33C to 2.5V and the discharge capacity C1 is recorded. C1 / C0 is the rate discharge ratio.

[0160] (4) 25℃@80% SOH cycle test: The battery is charged to 3.65V at 0.33C constant current and constant voltage, then discharged at 0.33C, and the discharge capacity C0 is recorded. After that, it is fully charged at 0.33C constant current and constant voltage. After full charge, it is discharged at 0.33C constant current, and the discharge capacity C1 is recorded. The 0.33C charge and 0.33C discharge cycle is continued until the discharge capacity Cn / C0=70%, and the cycle number n is recorded.

[0161] See Table 3 for the results.

[0162] Table 3

[0163]

[0164] As shown in Table 3, the present invention can effectively improve the electrochemical performance of the battery by coating the phosphate positive electrode core with a lightweight sponge-like structure of coconut shell-based foam carbon. Compared with Example 1, the first efficiency of Example 1 is improved by 5%, the 3C constant current charging ratio is improved by 16.4%, the 3C rate discharge capacity is improved by 12.6%, and the 3C / 1C room temperature cycle number is improved by 41%.

[0165] By comparing Application Example 1 with Application Examples 4-5, it can be seen that too little or too much coconut shell-based foam carbon content will lead to poor first efficiency and rate performance of the battery, and the cycle performance will also be slightly deteriorated.

[0166] By comparing Application Example 1 with Application Examples 6-7, it can be seen that the two-stage hydrothermal treatment is conducive to obtaining foamed carbon with more uniform particle size and higher purity, which helps to improve the rate and cycle performance.

[0167] By comparing Application Example 1 with Comparative Application Examples 1-2, it can be seen that in Example 1, the coconut shell-based foam carbon-coated LiMnPO 4 The main material has less free carbon, which is beneficial to improve the electrical performance. 4 Without carbon coating, the initial efficiency, rate performance and cycle performance of the battery are greatly reduced. In Comparative Example 2, LiMnPO coated with a carbon coating layer formed by glucose 4 , resulting in a significant decrease in rate performance and cycle performance. In Comparative Example 2, the peanut-based foam carbon has more impurities, more free carbon, and uneven coating, resulting in its electrical performance being inferior to that of the coconut shell-based foam carbon-coated LiMnPO 4 .

[0168] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A coconut shell-based foamed carbon modified phosphate positive electrode material, characterized in that: The positive electrode material comprises a phosphate positive electrode core and a coconut shell-based foamed carbon coated on the surface of the phosphate positive electrode core.

2. The coconut shell-based foamed carbon modified phosphate positive electrode material according to claim 1, characterized in that: Taking the total mass of the positive electrode material as 100%, the mass fraction of the coconut shell-based foamed carbon is 2%-3%.

3. A method for preparing a coconut shell-based foamed carbon modified phosphate positive electrode material as claimed in claim 1 or 2, characterized in that: The preparation method comprises the following steps: (1) preparing coconut shell-based foamed carbon; (2) The phosphate positive electrode material is formed into a core slurry, and the coconut shell-based foamed carbon is formed into a shell slurry. The core slurry and the shell slurry are used for coaxial electrospinning to obtain the coconut shell-based foamed carbon modified phosphate positive electrode material.

4. The preparation method according to claim 3, characterized in that: The method for preparing the coconut shell-based foamed carbon in step (1) comprises the following steps: (a) pre-treating coconut shell to obtain coconut shell powder; (b) mixing coconut shell powder with an aldehyde substance and concentrated acid to obtain a mixed slurry, placing the mixed slurry in a reaction kettle, charging with a protective gas and performing a heating reaction to obtain a foamed coconut shell resin; (c) heat-treating the foamed coconut shell resin to obtain coconut shell-based foamed charcoal.

5. The preparation method according to claim 4, characterized in that: The pretreatment in step (a) is crushing and screening; Preferably, in step (b), the aldehyde substance comprises at least one of formaldehyde, octanal, nonanal, decanal and undecanal; Preferably, in step (b), the mass ratio of the coconut shell powder to the aldehyde substance is (5-15):1; Preferably, the concentrated acid in step (b) comprises at least one of concentrated sulfuric acid, concentrated sulfuric acid and concentrated nitric acid; Preferably, the concentration of the mixed slurry in step (b) is 1.5 mol / L-2 mol / L; Preferably, the heating reaction in step (b) comprises two stages, wherein the first stage is: heating to a first temperature and keeping the temperature; the second stage is: continuing to heat to a second temperature and keeping the temperature; Preferably, the first temperature is 300°C-400°C, and the insulation time at the first temperature is 12h-36h; Preferably, the second temperature is 500°C-650°C, and the holding time at the second temperature is 5h-10h; Preferably, the pressure of the heating reaction in step (b) is 1 MPa-5 MPa; Preferably, the temperature of the heat treatment in step (c) is 700° C.-800° C.; Preferably, the heat treatment time in step (c) is 3h-6h.

6. The preparation method according to any one of claims 3 to 5, characterized in that: The core slurry in step (2) is obtained by dispersing a phosphate positive electrode material and a first surfactant in an organic solvent; Preferably, the first surfactant comprises at least one of polyurethane and CTAB; Preferably, the mass ratio of the phosphate positive electrode material to the first surfactant is 90:(0.5-1.5), and the concentration of the core slurry is 6 mol / L-8 mol / L; Preferably, the shell slurry is obtained by dispersing coconut shell-based foamed carbon and a second surfactant in an organic solvent; Preferably, the second surfactant comprises at least one of polyurethane and CTAB; Preferably, the mass ratio of coconut shell-based foamed carbon to the second surfactant is 80:(0.5-1.5), and the concentration of the shell slurry is 1.5 mol / L-2 mol / L; Preferably, the voltage of the coaxial electrospinning in step (2) is 20 kV-40 kV; Preferably, the spinning rate of the coaxial electrospinning in step (2) is 5 mL / min-15 mL / min; Preferably, the method further comprises the steps of washing and spray drying the product after the electrospinning in step (2).

7. A positive electrode slurry, characterized in that: The positive electrode slurry is obtained by homogenizing the coconut shell-based foamed carbon modified phosphate positive electrode material according to claim 1 or 2.

8. A method for homogenizing a positive electrode slurry as claimed in claim 7, characterized in that: The homogenization method comprises the following steps: After mixing the coconut shell-based foam carbon modified phosphate positive electrode material with the conductive agent and the binder, adding an organic solvent at least three times, stirring after each addition of the organic solvent, to obtain a positive electrode slurry; The amount of organic solvent added in the latter step is greater than the amount of organic solvent added in the previous step.

9. A positive electrode, characterized in that The positive electrode is prepared using the positive electrode slurry described in claim 7.

10. A battery, characterized in that: The battery comprises the positive electrode according to claim 9.

Citation Information

Patent Citations

  • Amorphous carbon negative electrode material as well as preparation method and application thereof

    CN112531160A

  • Preparation method of lithium iron phosphate electrode formed by foam material and battery

    CN112928239A

  • Lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof

    CN115954460A

  • Preparation method of lithium ion battery material

    CN117623299A

  • Surface-modified lithium-rich manganese-based positive electrode material and preparation method thereof

    CN118658968A